2012
DOI: 10.1136/bmjopen-2012-001386
|View full text |Cite
|
Sign up to set email alerts
|

Economic crisis and smoking behaviour: prospective cohort study in Iceland

Abstract: ObjectiveTo examine the associations between the 2008 economic collapse in Iceland and smoking behaviour at the national and individual levels.DesignA population-based, prospective cohort study based on a mail survey (Health and Wellbeing in Iceland) assessed in 2007 and 2009.SettingNational mail survey.ParticipantsRepresentative cohort (n=3755) of Icelandic adults.Main outcome measureSmoking status.ResultsA significant reduction in the prevalence of smoking was observed from 2007 (pre-economic collapse) to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 25 publications
2
52
0
5
Order By: Relevance
“…Smokers may be citing an increase in perceived stress to justify their relapse or failure to quit, and they are unable to quit their ongoing behaviour because of the offsetting increase in stress, thus falling into a vicious circle [74][75][76][77][78][79]. However, other studies have reported that economic recession is associated with a decline in the prevalence of cigarette smoking [1] and that a crisis may be health promoting [68,[80][81][82]. The effects on smoking behaviour appear to be largely influenced by price increases [1].…”
Section: Respiratory Mortality In Greece Amid An Economic Crisismentioning
confidence: 99%
See 1 more Smart Citation
“…Smokers may be citing an increase in perceived stress to justify their relapse or failure to quit, and they are unable to quit their ongoing behaviour because of the offsetting increase in stress, thus falling into a vicious circle [74][75][76][77][78][79]. However, other studies have reported that economic recession is associated with a decline in the prevalence of cigarette smoking [1] and that a crisis may be health promoting [68,[80][81][82]. The effects on smoking behaviour appear to be largely influenced by price increases [1].…”
Section: Respiratory Mortality In Greece Amid An Economic Crisismentioning
confidence: 99%
“…Reduced disposable income has been the main driver of this decline potentially leading to a significant long-term health gain [1], as it has transformed cigarettes into luxury goods [1,81]. Additional research in that direction actually characterises cigarette smoking as a cause of stress and, furthermore, smoking cessation as a valuable way to break the stress cycle [80][81][82][83]. Finally, a former smoker who experiences a drop in income may be less tempted to start smoking again because of the reduced affordability of cigarettes [84,85].…”
Section: Respiratory Mortality In Greece Amid An Economic Crisismentioning
confidence: 99%
“…21,25,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] While there is evidence of a decrease in overall alcohol consumption during recessions, 5,53 studies also consistently find an increase in alcohol related traffic accidents 55 (despite an overall decline in deaths from road traffic accidents), binge drinking, 5 and alcohol related hospitalization during economic contractions. 25 In other words, while on average some people reduce their drinking of alcohol, a subpopulation increases its use to potentially dangerous levels, reflecting that the hypotheses above may apply variously to different groups.…”
Section: Substance Abuse and Mental Healthmentioning
confidence: 99%
“…[7][8][9][10][11][12] On the other hand, some of the most recent studies based on ex-post analysis of smoking behaviour after the 2008 financial crisis reported a null or even a counter-cyclical relationship (the crisis increased tobacco smoking), possibly explained by an increased psychological stress in selected vulnerable populations. [13][14][15][16][17][18][19][20] In the UK, for instance, the attempt rates for smoking cessation steadily declined after the onset of the economic crisis.…”
Section: Introductionmentioning
confidence: 99%